2021
DOI: 10.18038/estubtda.913914
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polymer Concentration and Temperature on Micellization of Cetyltrimethylammnium Bromide (Ctab) in Aqueous PVP-Ctab Mixed System

Abstract: Polymeric micelles supply an environment, which can be cautiously regulated for drug delivery. The self-assembly of polymeric micellization is dynamic. Micellization thermodynamic describes how the system defines the formation of micelles. The present study enables the micellization behavior of the surfactants in the presence of polymer to be examined by conductometric and tensiometric methods. The effects of polymer concentration and temperature on the micellization thermodynamics of a neutral soluble polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
2
1
0
Order By: Relevance
“…This is a common occurrence for the aggregation of surface active materials [ 25 , 51 ]. A similar pattern was reported by Masalci [ 54 ], where the Δ G 0 values follow the trend we noticed. It is also reported by Masalci [ 54 ] that Δ G 0 is shown to fall to higher negative values as the temperature rises when the polymer is increased in quantity.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This is a common occurrence for the aggregation of surface active materials [ 25 , 51 ]. A similar pattern was reported by Masalci [ 54 ], where the Δ G 0 values follow the trend we noticed. It is also reported by Masalci [ 54 ] that Δ G 0 is shown to fall to higher negative values as the temperature rises when the polymer is increased in quantity.…”
Section: Resultssupporting
confidence: 92%
“…A similar pattern was reported by Masalci [ 54 ], where the Δ G 0 values follow the trend we noticed. It is also reported by Masalci [ 54 ] that Δ G 0 is shown to fall to higher negative values as the temperature rises when the polymer is increased in quantity. In the absence of electrolytes in the solution, Δ G 0 1,m values become more negative as the temperature rises, eventually remaining nearly constant.…”
Section: Resultssupporting
confidence: 92%
“…PEG increased cmc of a cationic surfactant of cetyldiethylethanolammonium bromide . Another study indicated that change in cmc of cetyltrimethylammomium bromide was a little in 0.5–2.0% polyvinylpyrrolidone solutions . Eudragit E100, a cationic polymethylmethacrylate, destabilized micelles of sodium dodecyl sulfate (anionic surfactant) .…”
Section: Results and Discussionmentioning
confidence: 99%